Abuse of Circumstances as Grounds for Cancellation of Transfer of Rights (Study of Decision Number 186/Pdt.G/2024/Pn Skt) - Anya Diyang Roseandi Dewi; Ariy Khaerudin; Femmy Silaswati Faried (LEGAL BRIEF, 2025)
This research examines the application of the concept of undue influence (misbruik van omstandigheden) as an indication for the cancellation of the transfer of rights in Indonesian civil law, specifically through an analysis of Surakarta District Court Decision Number 186/Pdt.G/2024/Pn Skt. Although not explicitly regulated in Indonesian Civil Code, this concept has gained judicial recognition through court decisions and jurisprudence. Undue influence occurs when an agreement is formed under conditions of disparity, where one party takes advantages of the economic or psychological weakness of the other party to obtain unfair benefits. This research uses a normative legal research method with a conceptual approach, examining secondary data through a literature study consisting of primary, secondary, and tertiary legal materials. The data analysis was conducted qualitatively through the stages of data reduction, data representation, and conclusion making. The result of the study show that the concept of undue influence is applied in Indonesian civil law based on open contract law system, the principles of freedom of contract and good faith, as well as the doctrine of unlawful acts. In decision number 186/Pdt.G/2024/Pn Skt, the judges identified five elements of undue influence, including circumstances that weaken the position of the plaintiffs, an unequal power relationship, exploitation of the circumstances by the defendant, lack of freedom of will, and conflict with decency, justice, and humanity.